Clonal integration increases relative competitive ability in an invasive aquatic plant. Issue 12 (13th December 2016) - Wang, Pu; Alpert, Peter; Yu, Fei‐Hai
Abstract : PREMISE OF THE STUDY: Physiological integration between connected ramets is well known to increase performance of clonal plant species. However, no direct evidence appears to exist that integration can increase the ability of clonal species to compete with other species within mixed communities. We tested this hypothesis using two floating, invasive, aquatic species in which fragmentation—and thus extent of integration—is likely to vary between habitats and times. METHODS: Individual ramets of Pistia stratiotes and Eichhornia crassipes were grown in monoculture or in mixture, and new stolons bearing new offspring were severed or left intact. After 6 wk, the numbers of offspring and second‐generation (2°) offspring produced by each original ramet, or parent, were counted; and the final dry mass of each parent, its stolons, its offspring, and its 2° offspring were measured. KEY RESULTS: Fragmentation decreased the relative competitive ability of Pistia, but not that of Eichhornia . This was mainly because Pistia accumulated ∼30% less dry mass of offspring when fragmented and grown with Eichhornia than in other treatments. Offspring of Pistia were smaller than those of Eichhornia in all treatments. CONCLUSIONS: Our results show that clonal integration can increase competitive ability in some clonal species. In this case, integration appeared to enable the small offspring of Pistia to compete more effectively with the large offspring of Eichhornia . Lower rates of fragmentation may select for production of more numerous, smaller vegetative offspring in clonal species.